2022
DOI: 10.1002/cjce.24366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods for the sequential extraction of lignite pretreated by ionic liquid

Abstract: In order to improve the extraction rate of coal by solvent extraction, Lianhuatang lignite (LHT) was pretreated with 1‐butyl‐3‐methylimidazolium hexafluorophosphate ionic liquid([Bmim]PF6) firstly. Then, the Soxhlet extraction (SE), ultrasound‐assisted extraction (UAE), and microwave‐assisted extraction (MAE) were carried out to obtain extracts (ES1‐3, EU1‐3, and EM1‐3) and residues (RS1‐3, RU1‐3, and RM1‐3) from the Lianhuatang lignite pretreated with ionic liquid (BLHT), respectively, and CS2, acetone, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For instance, Sönmez et al 26 . found that the extraction yield of lignite could be increased by adding [Bmim]Cl into NMP, and Ding et al 27 . pretreated Lianhuatang lignite with 1‐butyl‐3‐methylimidazolium hexafluorophosphate ionic liquid first, and sequentially extracted lignite by CS 2 , acetone and ethanol to explore the molecular composition of the extracted coal by various extractants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Sönmez et al 26 . found that the extraction yield of lignite could be increased by adding [Bmim]Cl into NMP, and Ding et al 27 . pretreated Lianhuatang lignite with 1‐butyl‐3‐methylimidazolium hexafluorophosphate ionic liquid first, and sequentially extracted lignite by CS 2 , acetone and ethanol to explore the molecular composition of the extracted coal by various extractants.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, mixed solvents have been paid much attention for their more efficient extraction capacity than single solvents during lignite extraction, and also sequential extraction of lignite is an effective method for chemical acquisition. 5 For instance, Sönmez et al 26 found that the extraction yield of lignite could be increased by adding [Bmim]Cl into NMP, and Ding et al 27 pretreated Lianhuatang lignite with 1-butyl-3-methylimidazolium hexafluorophosphate ionic liquid first, and sequentially extracted lignite by CS 2 , acetone and ethanol to explore the molecular composition of the extracted coal by various extractants. These methods provide a good reference for the utilization of lignite.…”
mentioning
confidence: 99%